THE RELATIONSHIP BETWEEN CELEBRITY WORSHIP AND CONSUMPTIVE BEHAVIOR IN TEENAGE K-POP FANS ON SOCIAL MEDIA X (TWITTER) - Putri, Febyani Amanda; Widyastuti (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The Korean Wave, or Hallyu, phenomenon has spread globally, especially among teenage K-pop fans on social media X (Twitter). Teenage K-pop fans often show consumptive behavior by buying items used by their idols. This study aims to determine the relationship between celebrity worship and consumptive behavior in teenage K-pop fans on social media X (Twitter). Method: This study uses quantitative methods with a correlational approach. The subjects of this study were teenage K-pop fans who were members of the WTS / WTB / WTT All Fandom community on Twitter, which had not been widely studied before. The sample size of this study was 204 respondents, which was calculated using the Jacob Cohen formula. This study uses two measuring instruments, namely the consumptive behavior scale and the celebrity worship scale. The consumptive behavior scale is measured based on the aspects proposed by Fromm with a reliability value of r = 0.889. Meanwhile, the celebrity worship scale is measured based on three aspects formulated by Maltby et al with a reliability value of r = 0.894. Results: The results of this study indicate that there is a positive relationship between celebrity worship and consumptive behavior in adolescent K-pop fans on social media X (Twitter), with a Pearson correlation value of r = 0.756 and getting a significance level of 0.001 (P < 0.05). Novelty: This means that the higher the level of celebrity worship, the higher the consumptive behavior of teenage K-Pop fans on social media X (Twitter). Conversely, if the level of celebrity worship is low, then the consumptive behavior also tends to be low.